Stability data of extemporaneous suspensions of hydroxychloroquine sulphate in oral liquid bases after tablet manipulation - Mara Perrone (Data in Brief, 2020)
Hydroxychloroquine is a well-known anti-malarial and anti-rheumatic drug that has garnered recently unprecedented attention as potential therapeutic agent against virus infections. Hydroxychloroquine sulphate is authorized in the EU as film-coated tablets (i.e. Plaquenil®), which cannot be administered to non-cooperative patients, such as those in intensive care units or, more in general, unable to swallow solid dosage forms. Therefore, the hospital pharmacist must manipulate the solid dosage form for the preparation of suspension, even if it can strongly affect the product quality. In this scenario, it is crucial to offer useful information and advice to assist hospital pharmacists in their activity. The data presented in this article suggest that extemporaneous suspensions of hydroxychloroquine sulphate in oral liquid bases after tablet manipulation are stable for at least 30 days.